Power Distribution and Possible Influence on Fuel Failure in WWER-1000 - Ján Mikuš (Science and Technology of Nuclear Installations)
The work is focused on the influence of investigation of some core heterogeneities and construction materials on the space power (fission rate) distribution in WWER-1000-type cores, especially from viewpoint of the values and gradient occurrence that could result in static loads with some consequences, for example, fuel pin (FP) or fuel assembly (FA) bowing and possible contribution to the FP failure root causes. For this purpose, experimental data and their analysis from two earlier performed measurements on light water, zero-power reactor LR-0 were used, concerning the relative radial power distribution determined by measurements in a WWER-1000-type core containing single FPs with homogeneous gadolinium admixture (Gd2O3) and the relative radial power distribution determined by measurements in FA situated on the periphery of a WWER-1000-type core neighbouring the baffle (thermal shielding).